Awareness and willingness to perform CPR: a survey amongst Flemish schoolchildren, teachers and principals. Issue 5 (3rd September 2019) - De Smedt, Lieven; Depuydt, Catheline; Vekeman, Eva; De Paepe, Peter; Monsieurs, Koenraad G.; Valcke, Martin; Mpotos, Nicolas
Abstract: Objectives: Training children in cardiopulmonary resuscitation (CPR) is one of the strategies to increase bystander CPR in society. Reinforcing knowledge and awareness and increasing willingness to perform bystander CPR contributes to a better outcome after cardiac arrest. We questioned schoolchildren, teachers and principals about their awareness of the importance of CPR and about their willingness to perform CPR. Methods: During a four-month period, Flemish schoolchildren aged 10–18 years, teachers and principals were invited to complete a survey consisting of three parts: (1) demographics, (2) CPR (training) experience and (3) attitude towards CPR teaching and training. Result: In total, 390 schoolchildren, 439 teachers and 100 principals completed the survey. Previous CPR training was reported by 33% of the schoolchildren (in 82% as part of the curriculum) and by 81% teachers and 82% principals. Willingness to participate in CPR training was 77% in schoolchildren, 79% in teachers and 86% in principals with 88% of the principals convinced that schoolchildren should learn how to perform CPR. Willingness to perform CPR in a real-life situation was 68% in schoolchildren, 84% in teachers and 92% in principals. Conclusion: Schoolchildren are well aware of the importance of CPR and are willing to acquire the related knowledge and skills. Noteworthy is the larger awareness among principals and teachers, establishing a strong base for increasing implementation of CPR training in schools. However, a majority of children indicated a lack of training opportunities, highlighting the need for a stronger implementation.